Action Implications and Connotations of Teacher Development: From the Perspective of Arendt's Action Theory - WANG Zhipeng; LIU Xudong (Jiaoshi jiaoyu xuebao)
Teacher development emphasizes the holistic development of teachers as specific and rich individuals, aiming to refocus teacher education on the lives of teachers themselves. Arendt's action theory understands action based on human life itself, elucidating the core connotations of action from three dimensions: self-purpose, mutual refinement, and active exploration. It highlights the unique value of action in human growth and provides important insights for grasping the action implications of teacher development from the perspective of life itself. Teacher development that embodies the implications of action is a self-purposeful activity that aligns with teachers' spiritual instincts. It is a process of mutual refinement that fits environmental changes and an indispensable active exploration activity that constitutes daily educational life. In the past, constrained by instrumental rational educational thinking, programmed educational models, and modern educational theories, teacher development was often seen as an additional activity outside of daily educational life, and its action implications were obscured. In the current era of pursuing high-quality development in teacher education, it is necessary to rediscover the meaning of action to promote the return of teacher development to daily educational life. Therefore, we should focus on teachers' changes in daily educational life, highlighting the true state of teacher development; Strengthen interpersonal communication and interactions in daily educational life, expanding the temporal and spatial boundaries of teacher development; and focus on problem-solving in daily educational life, promoting teachers' development through educational research.